Aspiration versus stent retriever thrombectomy for distal, medium vessel occlusion stroke in the posterior circulation: a subanalysis of the topmost study - Meyer, Lukas; Stracke, Paul; Wallocha, Marta; Broocks, Gabriel; Sporns, Peter; Piechowiak, Eike; Kaesmacher, Johannes; Maegerlein, Christian; Petzsche, Moritz Roman Hernandez; Dorn, Franziska; Zimmermann, Hanna; Naziri, Weis; et al. (Stroke, 2022)
Background: The optimal endovascular strategy for reperfusing distal medium-vessel occlusions (DMVO) remains unknown. This study evaluates angiographic and clinical outcomes of thrombectomy strategies in DMVO stroke of the posterior circulation. Methods: TOPMOST (Treatment for Primary Medium Vessel Occlusion Stroke) is an international, retrospective, multicenter, observational registry of patients treated for DMVO between January 2014 and June 2020. This study analyzed endovascularly treated isolated primary DMVO of the posterior cerebral artery in the P2 and P3 segment. Technical feasibility was evaluated with the first-pass effect defined as a modified Thrombolysis in Cerebral Infarction Scale score of 3. Rates of early neurological improvement and functional modified Rankin Scale scores at 90 days were compared. Safety was assessed by the occurrence of symptomatic intracranial hemorrhage and intervention-related serious adverse events. Results: A total of 141 patients met the inclusion criteria and were treated endovascularly for primary isolated DMVO in the P2 (84.4%, 119) or P3 segment (15.6%, 22) of the posterior cerebral artery. The median age was 75 (IQR, 62-81), and 45.4% (64) were female. The initial reperfusion strategy was aspiration only in 29% (41) and stent retriever in 71% (100), both achieving similar first-pass effect rates of 53.7% (22) and 44% (44; P=0.297), respectively. There were no significant differences in early neurological improvement (aspiration: 64.7% versus stent retriever: 52.2%; P=0.933) and modified Rankin Scale rates (modified Rankin Scale score 0-1, aspiration: 60.5% versus stent retriever 68.6%; P=0.4). In multivariable logistic regression analysis, the time from groin puncture to recanalization was associated with the first-pass effect (adjusted odds ratio, 0.97 [95% CI, 0.95-0.99]; P<0.001) that in turn was associated with early neurological improvement (aOR, 3.27 [95% CI, 1.16-9.21]; P<0.025). Symptomatic intracranial hemorrhage occurred in 2.8% (4) of all cases. Conclusions: Both first-pass aspiration and stent retriever thrombectomy for primary isolated posterior circulation DMVO seem to be safe and technically feasible leading to similar favorable rates of angiographic and clinical outcome.
Gesehen am 29.08.2022